Job burnout and resilience among palliative care professionals in china: a qualitative study - Fang Tan; Yan Wu; Na Li; Chuan Zhang; Shan Chen; Lan Huang; Yang Chen; Jianjun Jiang; Qian Deng (BMC Palliative Care)
Abstract Background Medical professionals who are engaged in palliative care commonly experience negative emotions resulting from the pain and grief experienced by patients and family members, which results in enormous psychological pressure for professionals, and the risk related to job burnout is significantly greater. Objective We aimed to explore the factors influencing job burnout and resilience among palliative care professionals. Methods We conducted a qualitative study using semistructured interviews and purposeful sampling methods. Face-to-face interviews were carried out from September 2023-April 2024 in the palliative care ward of one of the top three hospitals in a province of China. A total of 22 palliative care professionals were interviewed. The interview data were coded and relevant topics were extracted and summarized from two perspectives: factors influencing job burnout among palliative care professionals and resilience to job burnout. Data analysis was guided by Colaizzi’s seven-step method. Results This study identified personal, work, institutional, and social factors affecting job burnout among palliative care professionals in China. Personal factors include the original intention of engaging in palliative care, psychological qualities, and ways of coping with stress. Work factors include work intensity and environment and the characteristics and nature of palliative care work. Institutional and social factors include promotion mechanisms, wages and benefits, government policy support and professional recognition, as well as cultural conflicts from traditional China. The factors that affect resilience include personal internal factors and external factors. Personal internal factors come from good self-regulation and emotional balance, while external factors come from an increasingly sophisticated social support system and effective intervention measures to cope with job burnout. Conclusion Our research found that many factors affect the job burnout and resilience of palliative care professionals. Promoting the construction of a professional team in palliative medicine, rational allocation of human resources, improving the welfare benefits of professionals, enhancing their social status, safeguarding their legitimate rights and interests, establishing effective emotional and social support systems, and implementing effective intervention measures in cultural contexts are all effective ways to reduce work fatigue and enhance resilience. Future research needs to investigate intervention measures to address or prevent burnout.